CLASSICAL EXPERIMENT IN CINE MUSIC: सिने संगीत में शास्त्रीय प्रयोग - Verma, Harish (International Journal of Research -GRANTHAALAYAH, 2015)
Indian films cannot be imagined without music. The hallmark of Indian cinema is its vibrant music. Indian films, whether they are in any language (ie Hindi, Tamil, Bengali, Marathi, Telugu, Kannada or Malayalam), music predominates. Music is their basic element in films made in regional dialects like Bhojpuri, Rajasthani, Bandeli, Chhattisgarhi etc. Most of the films in India are made in Hindi language which are popular all over the world. Hence, we will discuss about Indian films by keeping Hindi films at the center. संगीत के बिना भारतीय फिल्मों की कल्पना भी नहीं की जा सकती। भारतीय सिनेमा की पहचान उसका सषक्त संगीत ही है। भारतीय फिल्में चाहे वे किसी भी भाषा (अर्थात् हिन्दी, तमिल, बंगाली, मराठी, तेलुगु, कन्नड़ या मलयालम) की हों, संगीत उनमें प्रमुख होता है। क्षेत्रीय बोलियों जैसे भोजपुरी, राजस्थानी, बंुदेली, छत्तीसगढ़ी आदि में बनने वाली फिल्मों में तो संगीत ही उनका मूल तत्व होता है। भारत में सर्वाधिक फिल्में हिन्दी भाषा में बनती हैं जो विश्व भर में लोकप्रिय होती हैं। अतः आगे हम भारतीय फिल्मों की चर्चा हिन्दी फिल्मों को केन्द्र में रखकर ही करेंगे।